The Impact of Obligation to Assignment of Ownership (TamlÄ«k) in ImÄmÄ« Jurisprudence and Iranian Law - Ã™Â†Ã˜Â¹Ã™Â…Ã˜Âª Ã˜Â§Ã™Â„Ã™Â„Ã™Â‡Ã›ÂŒ, Ã˜Â§Ã˜Â³Ã™Â…Ã˜Â§Ã˜Â¹Ã›ÂŒÃ™Â„ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
In ordinary cases, the object of transaction in such contracts as sale (bayâ) and lease (ijÄra) has financcial value like property (âayn) or profit, or physical action. However, whether obligation to performing an action has a financial value and can be the object of transaction is a matter of debate. In adition, in cases in which the subject of the obligation is the assignment of ownership (tamlÄ«k) of a specific or general property, the question arises as to whether the obligation causes the ownership or claim for the obligee regarding that specific or general property. This article seeks to prove that the legal action has financial value and it can be taken as the object of transaction; however, such an action is normally actualized simply in the form of settlement of a claim (á¹£ulá¸¥) or an independent and anonymous contract as well as condition within the contract. Legal action, of course, has no direct financial value. For this reason, in cases in which the subject of the obligation is the assignment of ownership of a specific or general property, the impact of such dealing is simply the appearance of duty to fulfill the obligation with its specific impacts. The appearance of this duty does not have any correlation with the appearance of the obligeeâs ownership for that specific or general property or any debt to the value of the undertaken action.